2018
DOI: 10.1002/aenm.201802790
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Spatial Variations of Optical Bandgaps in Perovskite Solar Cells

Abstract: their optical and electrical properties. A common optical-based approach to estimate bandgaps of direct-gap semiconductors is to employ absorption spectroscopy. In this approach, one captures absorption spectra of materials and obtains absorption thresholds from Tauc plots. [3] The Tauc analysis provides a consistent way to compare among materials. However, as mentioned by Green et al., [4] these thresholds represent optical bandgaps, not electronic bandgaps, as the Tauc analysis underestimates the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…The PL intensity is determined by several mechanisms-light-induced trap deactivation, ion migration under light excitation, and actual degradation due to air exposure. [31] Thus, the spectral peak location and A are not affected. [30] Thus, location A (affected by air exposure initially) and location B (representative for areas unaffected by air exposure initially) have different PL intensity trends (Figure 6a).…”
Section: Results and Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…The PL intensity is determined by several mechanisms-light-induced trap deactivation, ion migration under light excitation, and actual degradation due to air exposure. [31] Thus, the spectral peak location and A are not affected. [30] Thus, location A (affected by air exposure initially) and location B (representative for areas unaffected by air exposure initially) have different PL intensity trends (Figure 6a).…”
Section: Results and Analysismentioning
confidence: 98%
“…Depending on the material and device quality at each location, its response rate to each mechanism varies. [31] However, under the air exposure, the material degrades and its PL spectrum shows a red shift and a reduction in intensity (see Figure S6, Supporting Information, for the data on bare perovskite films). Under the lightinduced trap deactivation and ion migration, the PL intensity is altered whereas the PL spectral shape is identical.…”
Section: Results and Analysismentioning
confidence: 99%
“…Perovskite modules are investigated for layer inhomogeneities using the described five-step characterization procedure. Two of the five steps in the process are based on perovskite luminescence images, where due to temporal changes in device luminescence, [37,[39][40][41][42][43] we used the same measurement method for all analyzed samples (see Supporting Information). The characterization procedure was used to detect and analyze inhomogeneities with the highest resolution of 10 μm.…”
Section: Resultsmentioning
confidence: 99%
“…In perovskite-based PV, there are multiple studies where photoluminescence (PL) mapping has been used to analyze heterogeneity in perovskite films on grain-size scales, including bandgap variations, charge-carrier dynamics, stability, and so forth. [37][38][39] Recently, Mundt et al [36] demonstrated a spatially resolved analysis of efficiency loss in perovskite solar cells (PSCs) based on dark lock-in thermography (DLIT) and multiwavelength light-beam induced current (LBIC). Local layer inhomogeneities were revealed to contribute major loss in cells with an active area of 1.1 cm 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation